Effectiveness and safety of fibrinolytic therapy in critically ill patients with COVID-19 with ARDS: protocol for a prospective meta-analysis. Issue 9 (26th September 2022) - Kovács, Emőke Henrietta; Dembrovszky, Fanni; Ocskay, Klementina; Szabó, László; Hegyi, Péter; Molnar, Zsolt; Tánczos, Krisztián
Abstract : Introduction: The use of fibrinolytic therapy has been proposed in severe acute respiratory distress syndrome (ARDS). During the COVID-19 pandemic, anticoagulation has received special attention due to the frequent findings of microthrombi and fibrin deposits in the lungs and other organs. Therefore, the use of fibrinolysis has been regarded as a potential rescue therapy in these patients. In this prospective meta-analysis, we plan to synthesise evidence from ongoing clinical trials and thus assess whether fibrinolytic therapy can improve the ventilation/perfusion ratio in patients with severe COVID-19-caused ARDS as compared with standard of care. Methods and analysis: This protocol was registered in PROSPERO. All randomised controlled trials and prospective observational trials that compare fibrinolytic therapy with standard of care in adult patients with COVID-19 and define their primary or secondary outcome as improvement in oxygenation and/or gas exchange, or mortality will be considered eligible. Safety outcomes will include bleeding event rate and requirement for transfusion. Our search on 25 January 2022 identified five eligible ongoing clinical trials. A formal search of MEDLINE (via PubMed), Embase, CENTRAL will be performed every month to identify published results and to search for further trials that meet our eligibility criteria. Dissemination: This could be the first qualitative and quantitative synthesis summarising evidence of the efficacy and safety of fibrinolytic therapy in critically ill patients with COVID-19. We plan to publish our results in peer-reviewed journals. PROSPERO registration number: CRD42021285281.